Fracture at all scales - Pluvinage, Guy; Milovic, Ljubica (Springer, 2016)
This book is a compilation of selected papers from the 2014 New Trends in Fatigue and Fracture (NT2F14) Conference, which was held in Belgrade, Serbia. This prestigious conference brought together delegates from around the globe to discuss how to characterize, predict and analyze the fatigue and fracture of engineering materials, components, and structures using theoretical, experimental, numerical and practical approaches. It highlights some important new trends in fracture mechanics presented at the conference, such as: - two-parameter fracture mechanics, arising from the coupling of fracture toughness and stress constraints - high-performance steel for gas and oil transportation and production (pressure vessels and boilers) - safety and reliability of welded joints This book includes 12 contributions from well-known international scientists and a special tribute dedicated to the scientific contributions of Stojan Sedmark, who passed away in 2014.- Resumé vydavatel
2 Some Industrial Applications of the Two Fracture Mechanics Approach.
Keywords: lomová mechanika; fracture mechanics; elektronické knihy; sborníky konferencí; electronic books; proceedings of conferences